2017
DOI: 10.1063/1.4977467
|View full text |Cite
|
Sign up to set email alerts
|

MHD modeling of a DIII-D low-torque QH-mode discharge and comparison to observations

Abstract: Extended-MHD modeling of DIII-D tokamak [J. L. Luxon, Nucl. Fusion 42, 614 2002] QH-mode discharges with nonlinear NIMROD [C. R. Sovinec et al., JCP 195, 355 2004] simulations saturates into a turbulent state, but does not saturate when the steady-state flow inferred from measurements is not included. This is consistent with the experimental observations of the quiescent regime on DIII-D. The simulation with flow develops into a saturated turbulent state where the n φ =1 and 2 toroidal modes become dominant t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
(37 reference statements)
0
14
2
Order By: Relevance
“…Section 5.7 finally, contains a very brief outlook. For investigations of ELMs and ELM control with other non-linear MHD codes, refer to the review provided in reference [3] and for more recent work to references [181][182][183][184][185][186][187][188][189][190][191] and references therein.…”
Section: Applications To Elms and Elm Controlmentioning
confidence: 99%
“…Section 5.7 finally, contains a very brief outlook. For investigations of ELMs and ELM control with other non-linear MHD codes, refer to the review provided in reference [3] and for more recent work to references [181][182][183][184][185][186][187][188][189][190][191] and references therein.…”
Section: Applications To Elms and Elm Controlmentioning
confidence: 99%
“…Nonlinear simulation with the JOREK code solving the reduced MHD model derived from the visco-resistive MHD equations also showed that the kink/peeling mode is the most unstable mode and is saturated non-linearly in QH-mode plasmas [8,9]. Nonlinear simulation using the NIMROD code with a resistive MHD model including an anisotropic stress tensor and anisotropic thermal heat conduction did not identify the branch of MHD mode unstable in a DIII-D QH-mode plasma, but indicated that MHD modes with low toroidal mode numbers are unstable and can be saturated as quasi-turbulent state when taking into account plasma rotation [10], where an MHD mode with low toroidal mode number is usually current-driven one.…”
Section: Introductionmentioning
confidence: 97%
“…The excitation mechanism of such instabilities is still unclear. Previous theoretical interpretations suggested that short wavelength modes exhibiting infernal features [13][14][15][16], though dominant in the linear phase, were suppressed nonlinearly and superseded by steady low-n modes [17,18] with no significant effects of the parallel flow [17,19]. Recent experimental findings point to the E × B shearing rate as the key ingredient for the development of the characteristics of these oscillations [19].…”
mentioning
confidence: 99%